2015
DOI: 10.1620/tjem.237.117
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of EBV-Encoded microRNAs in EBV-Associated Hemophagocytic Lymphohistiocytosis

Abstract: Epstein-Barr virus-associated hemophagocytic lymphohistiocytosis (EBV-HLH) is a life-threatening complication of EBV infection. MicroRNAs (miRNAs) were small non-coding RNA, and EBV could encode miRNAs that are involved in the progression of infection. However, the profiles of EBV-miRNAs in EBV-HLH were unknown. Here, we aimed to profile the expression of EBV-miRNAs in children with EBV-HLH by analyzing 44 known EBV-miRNAs, encoded within the BamHI fragment H rightward open reading frame 1 (BHRF1) and the BamH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 40 publications
(47 reference statements)
2
20
0
Order By: Relevance
“…Interestingly, the inhibition of NK cell cytotoxicity following severe influenza virus infections was related to the viral load, suggestive of a dose-dependent effect of this immunoevasive mechanism ( 66 ). In EBV-associated HLH, surprisingly higher viral loads are detected when compared to other EBV-associated diseases like infectious mononucleosis ( 33 , 81 ), indicating that EBV-encoded immunoevasion strategies may exert a more pronounced effect in EBV-HLH as well. Supporting this hypothesis, decreased perforin levels and reduced cytotoxicity were uniquely detected in infected T cells from patients with EBV-associated secondary HLH, not in infected NK cells from patients with chronic active EBV disease ( 82 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the inhibition of NK cell cytotoxicity following severe influenza virus infections was related to the viral load, suggestive of a dose-dependent effect of this immunoevasive mechanism ( 66 ). In EBV-associated HLH, surprisingly higher viral loads are detected when compared to other EBV-associated diseases like infectious mononucleosis ( 33 , 81 ), indicating that EBV-encoded immunoevasion strategies may exert a more pronounced effect in EBV-HLH as well. Supporting this hypothesis, decreased perforin levels and reduced cytotoxicity were uniquely detected in infected T cells from patients with EBV-associated secondary HLH, not in infected NK cells from patients with chronic active EBV disease ( 82 ).…”
Section: Discussionmentioning
confidence: 99%
“…More highly elevated levels of EBV-encoded microRNAs (miRNAs) (BamHI A rightward transcripts miRNAs, another class of immunoevasins) were reported in patients with EBV-HLH compared to patients with EBV-associated infectious mononucleosis, urging the authors to speculate a role for these miRNAs in HLH pathogenesis. Levels of one specific miRNA, the antiapoptotic BART16-1 ( 83 ), even correlated with disease activity and remission ( 81 ). In this light, virus-encoded evasins may constitute novel biomarkers to track disease severity, evaluate treatment responses, or predict progression from acute infection to virus-associated HLH.…”
Section: Discussionmentioning
confidence: 99%
“…Kawano et al [ 24 ] pointed out that the levels of miR-BART2-5p, 13, and 15 in plasma correlated with the severity and prognosis of CAEBV. Zhou et al [ 25 ] found that levels of several EBV-miRNAs (miR-BART3-3p, 3-5p, 1-3p, 1-5p, 15–1, 5-3p, and 16–1 et al) in Epstein-Barr virus-associated hemophagocytic lymphohistiocytosis (EBV-HLH) were higher than in IM and healthy controls, and suggested that plasma miR-BART16-1 could be a potential biomarker for monitoring EBV-HLH progression.…”
Section: Discussionmentioning
confidence: 99%
“…Primary infection with EBV in adolescence frequently results in acute infectious mononucleosis (IM) [2]. In some cases, EBV can infect T cells and NK cells and induce chronic active EBV infection (CAEBV) [3], EBV-associated hemophagocytic lymphohistiocytosis (EBV-HLH) [4], and EBV-associated T/NK cell lymphoproliferative diseases [5]. CAEBV is classified as a lymphoproliferative disorder in the 2016 World Health Organization lymphoma classification [6].…”
Section: Introductionmentioning
confidence: 99%